The Effectiveness Of Using Restorative Justice Against Minor Corruption Crime In Achieve The Ultimum Remedium - Adinda Dwi Prestiwi; Hedy Dianisa Amin; Desliyona Desliyona (Corruptio, 2022)
Corruption is a habit that has been going on continuously among the people of Indonesia. Not only does it harm state finances, but it also injures the social and economic rights of the community, so corruption is classified as a great crime and requires extraordinary measures. So in the context of rescue and reform that requires a state that is free from corrupt behavior, it can be realized through developing progressive and just laws. In response to the resolution of the settlement of criminal acts, the Indonesian Attorney General's Office has issued regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice which is the settlement of criminal cases by prioritizing recovery from a crime that leads to progressive criminal law. Then how is the effectiveness of restorative justice against minor corruption crimes in realizing the ultimum remedium as criminal law, which is used as a last resort in law enforcement? As such this study aims to determine the effectiveness of the use of restorative justice against minor corruption in realizing the ultimum remedium. The type of research in this study uses library research, with the nature of descriptive research, and uses a normative juridical approach. The results of this study conclude that the effectiveness of the use of restorative justice against minor corruption crimes focuses on strengthening regulations in procedural terms while still referring to state financial losses and the presence or absence of means rea (evil intent) in realizing the prevention of minor corruption crimes to be resolved by an out-of-court process as an ultimum remedium step or a last resort in terms of law enforcement. Restorative justice is a legal effort to offer a comprehensive and effective solution for minor corruption cases.